Electricity Restructuring : The Implications for Air Quality. (U.S. Congressional Research., 2001)
Provides overview of electric industry restructuring and air emissions issues. Covers the debate on restructuring and the environment, the utility industry, environmental regulation, and impacts of restructuring on air quality.